Organizational Policy and Sexual Harassment as Predictors of Career Advancement among Female Bankers - Roberts , Enyelunekpo R.; Okurame, David E.; Odungweru, Dennis H.; Uye, Emmanuel E. (Pancasila International Journal of Applied Social Science, 2025)
Career advancement among females has continued to generate research interests among scholars. Studies have investigated career advancement among female bankers using different predictors with varied results. Therefore, this study investigated organizational policy and sexual harassment as predictors of career advancement among female bankers in Port Harcourt metropolis. A cross-sectional survey design was adopted, while a purposive sampling technique was used to select the study population. Data were conveniently collected from 250 participants using validated questionnaires and analyzed using multiple regression analysis to test one hypothesis at p =.001 significance level. The result indicated that organizational policy and sexual harassment jointly predicted career advancement among study participants [R2= .534, F(2, 227) = 130.006, p= .001]. Furthermore, organizational policy (β =.306, p =.001) and sexual harassment (β = -.642, p = .001) independently predicted career advancement among study participants. The study concludes that organizational policy and sexual harassment are robust predictors of career advancement among study participants. It is recommended that bank management put policies and programmes that are gender friendly and reduce sexual harassment germane to career advancement among female bankers.